Active packaging film containing oregano essential oil microcapsules and their application for strawberry preservation. Issue 10 (27th September 2020) - Li, Li; Song, Wenlong; Shen, Chunhua; Dong, Qingfeng; Wang, Yifen; Zuo, Sheng
Abstract: An active packaging film based on low‐density polyethylene (LDPE)/ethylene‐vinyl acetate (EVA) copolymer was prepared. Oregano essential oil microcapsules were prepared by spray drying and added as active antibacterial ingredients to the LDPE/EVA film by melt blending and extrusion casting and enhanced the moisture permeability and gas permeability of the film. The active packaging film effectively regulates the respiration of strawberries by delaying the accumulation of carbon dioxide and the reduction of oxygen in the package. The firmness, total soluble solids, titratable acid, malondialdehyde, and hydrogen peroxide content of strawberries were tested. Low‐field nuclear magnetic resonance (LF‐NMR), T2 relaxation time method, and a visualization method (MRI) were used to track the water status and migration of strawberry in different active film packages, and the change in the moisture content also indicated that the active film can effectively reduce the content and speed of free water produced by respiratory metabolism. Practical applications: As one of the common methods for fruits and vegetables preservation, active packaging is an important way to reduce consumption of fruits and vegetables and increase farmers' economic income. Controlling the respiration and reducing the loss of strawberries metabolism are one of the important means. We mainly develop an active packaging film that can reduce the respiration and inhibit the spoilage of strawberries. An active packaging film based on low‐density polyethylene (LDPE)/ethylene‐vinyl acetate (EVA) copolymer was prepared by melt blending and extrusion casting methods, and oregano essential oil microcapsules were used as an antibacterial agent. This active packaging film can be used in cold chain logistics and can also be used in supermarkets, stores, and homes. It can effectively extend the shelf life of strawberries due to the potentiality of the application of preservation technology.